FINANCIAL RATIO ANALYSIS OF YOGYAKARTA PROVINCE GOVERNMENT - Lestari Sukarniati; Nurul Azizah Az zakiyyah (Universitas Tidar, 2021)
Region financial independence indicates the ability of a government to finance its activities, the cost of development, and services to people concerning decentralization purposes. The objective of the research is to identify the level of financial independence of each regency and city in DIY Province, in which each promotes different potency. The quantitative method is employed in this research by using secondary data. Furthermore, the data are analyzed using the Panel Data method. The result demonstrates that in general the financial management in DIY Province is considered fair and resulted in the quite high financial condition index value.